Fern-based hard carbon material as well as preparation method and application thereof

A three-step process of low-ratio KOH weak etching, NH4CO3 synergistic activation, and low-temperature CVD sealing was used to construct fern-based hard carbon materials, which solved the problems of excessive specific surface area and uncontrollable pore structure of biomass hard carbon materials, and achieved high initial coulombic efficiency and long cycle stability, making it suitable for the large-scale production of sodium-ion battery anode materials.

CN121493946APending Publication Date: 2026-02-10INNER MONGOLIA SANLING LULING NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202512046508.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-31
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Existing biomass hard carbon materials suffer from problems such as excessively high specific surface area, uncontrollable pore structure, and insufficient interfacial conductivity in their preparation and application, resulting in low initial coulombic efficiency, limited plateau capacity improvement, and poor cycle stability.

Method used

By employing low-ratio KOH weak etching combined with NH4CO3 synergistic activation, along with low-temperature CVD and rapid annealing processes, a three-level structure consisting of a core layer, a transition layer, and an outer sealing layer is constructed. Through microporous networks, local sealing, and interfacial graphitization, the material achieves low specific surface area, high plateau capacity, and high conductivity.

Benefits of technology

Hard carbon materials with high initial coulombic efficiency, abundant sodium storage sites, and excellent cycle performance were prepared. These materials are suitable for use as anodes in sodium-ion batteries, exhibiting high reversible capacity and long lifespan. The process parameters are mild and controllable, and the cost is low, making them suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121493946A_ABST
    Figure CN121493946A_ABST
Patent Text Reader

Abstract

The invention discloses a fern-based hard carbon material as well as a preparation method and application thereof, and the preparation method comprises the following steps: grinding washed and dried fern into powder, and carrying out low-temperature pre-carbonization to obtain a pre-carbonized product; mixing the pre-carbonized product with a mixture activator of KOH and (NH4) 2CO3, and performing weak etching activation to obtain an etched product; carbonizing the etched product to obtain a hard carbon core; performing chemical vapor deposition on the hard carbon core to form a nitrogen-doped carbon hole sealing layer to obtain a surface hole sealing product; and finally, carrying out annealing treatment on the surface hole sealing product to obtain the fern-based hard carbon material. The hard carbon material with high initial coulombic efficiency, high reversible capacity and excellent cycling stability is prepared by adopting a three-step synergistic process of low-ratio activation, in-situ CVD and rapid annealing. The method is wide in raw material source, low in cost, mild and controllable in process parameters, relatively low in energy consumption and suitable for large-scale production of the sodium-ion battery negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy materials and energy storage electrode materials, and in particular to a fern-based hard carbon material, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries have shown great potential in large-scale energy storage due to their abundant resources and low cost. The anode material is one of the core components determining the energy density, cycle life, and other key performance characteristics of sodium-ion batteries. Hard carbon, as a typical non-graphitized carbon material, is considered a highly promising anode material for sodium-ion batteries due to its large interlayer spacing and abundant sodium storage sites. Among them, biomass-based hard carbon has attracted widespread attention due to its advantages such as wide availability of renewable raw materials and low cost.

[0003] However, existing biomass hard carbon materials still face a series of technical bottlenecks in their preparation and application. First, to obtain high capacity, strong bases (such as KOH) are often used for activation to create pores. However, this usually results in an excessively high specific surface area (SSA), leading to the formation of an excessively thick solid electrolyte interphase (SEI) film during the first charge-discharge cycle. This consumes a large amount of active sodium ions, resulting in a low initial coulombic efficiency (ICE). Second, the pore structure (mostly open pores) generated during activation is uncontrollable, with long ion diffusion paths and limited improvement in plateau capacity (corresponding to the filling behavior of sodium ions). Third, to reduce the specific surface area, chemical vapor deposition (CVD) is often used to deposit a carbon film on the material surface to seal the open pores. However, existing CVD techniques (such as high temperature and long-term use of carbon sources such as acetylene and benzene) often result in an excessively thick (>10 nm) or uneven sealing layer, which hinders the rapid transport of sodium ions. Finally, high-temperature graphitization to improve conductivity often comes at the cost of sacrificing sodium storage sites and may lead to embrittlement of the closed-pore structure, affecting cycle stability.

[0004] In existing technologies, for example, patent CN117776178A uses strong KOH activation combined with acetonitrile CVD for nitrogen doping and pore adjustment, but the resulting material still has a relatively high specific surface area. Patent CN118239487A uses KOH / K2CO3 composite activation combined with high-temperature pore closing and CVD pore plugging, resulting in a closed structure but high energy consumption and complex process. Acetylene CVD pore sealing technology reported in related literature can only achieve surface passivation, with limited optimization effects on internal pore structure and plateau capacity. Therefore, how to synergistically control the internal pore structure, surface chemical state, and interfacial conductivity of hard carbon materials to achieve a balance between low specific surface area, high plateau capacity, high initial efficiency, and long cycle life is a key problem urgently needing to be solved in this field. Summary of the Invention

[0005] This invention provides a fern-based hard carbon material, its preparation method, and its application, to overcome the problems of structural damage caused by strong activation, uncontrollable thickness of the sealing layer, and insufficient interfacial conductivity in existing technologies.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: This invention provides a method for preparing a fern-based hard carbon material, comprising the following steps: S1: Pretreatment: Grind the washed and dried ferns into powder to obtain biomass powder; S2: Pre-carbonization: Under an inert atmosphere, the biomass powder is heated to 300-500°C at a rate of 2-10°C / min and held for 1-5 hours to perform pre-carbonization, thereby obtaining a pre-carbonized product; the preferred pre-carbonization temperature is 350-450°C, the preferred time is 2-3 hours, and the preferred heating rate is 3-6°C / min. S3: Weak Etching Activation: The pre-carbonized product and activator are mixed at a mass ratio. After mixing, the mixture is heated to 600-800℃ at a rate of 2-10℃ / min under an inert atmosphere and held for 30-90 minutes. After cooling, weak etching activation is performed to obtain the etched product. The inert atmosphere is nitrogen or argon. The pre-carbonization temperature is preferably 350-450℃, the heating rate is preferably 3-6℃ / min, and the holding time is preferably 2-3 hours. This step is weak etching activation, which can achieve ion migration + chemical potential weak etching, forming a confined microporous network inside the particles. The sample is removed after cooling. This step achieves micro-activation, generating only limited micropores inside without forming a large specific surface area structure. K + With NH4 + Synergistic activation can induce the formation of local pores at low ratios, avoiding the high surface area caused by strong corrosion; S4: Medium-temperature carbonization: The etched product after washing and drying is heated to 1000-1200℃ at 2-10℃ / min under an inert atmosphere and held for 1-6 hours to obtain a hard carbon core HC-core; the heating rate is preferably 3~6℃ / min, the medium-temperature carbonization temperature is preferably 1100~1200℃, and the holding time is preferably 2~3 hours.

[0007] S5: In-situ heteroatom sealing: Under an inert atmosphere, the hard carbon core is placed in an environment of 600-800℃, and a mixture of acetylene, ammonia, and inert gas is introduced to perform chemical vapor deposition, forming a nitrogen-doped carbon sealing layer on the surface of the hard carbon core. After the carbon source is turned off, an inert atmosphere (nitrogen or argon) is continued to be introduced to cool to room temperature, and the surface sealing product HC-seal is obtained. The chemical vapor deposition temperature is preferably 700℃, and the deposition time is 10-15 minutes. In this step, acetylene is thermally decomposed to form a carbon layer, and NH3 thermal decomposition provides in-situ N doping, realizing the sealing of surface pores and the construction of a lightly doped passivation layer. S6: Post-processing: The sealing product is annealed in an inert atmosphere to improve film adhesion. The quasi-graphitization orientation of the outer carbon film is induced by thermal stress to promote the formation of interfacial conductive channels. After annealing, the fern-based hard carbon material is obtained. The obtained fern-based hard carbon material is washed with deionized water and dried at 80°C for 12 hours, then ground to obtain the fern-based hard carbon anode material for later use.

[0008] Further, in step S3, the mass ratio of KOH, (NH4)2CO3, and the pre-carbonized product is (0.05-0.2): (0.02-0.05):1.

[0009] Further, in step S5, the mixed gas is a mixture of acetylene and ammonia, with an acetylene flow rate of 3-5 sccm, an ammonia flow rate of 1-3 sccm, and a total mixed gas flow rate of 1000 sccm.

[0010] Furthermore, the inert gas is nitrogen or argon.

[0011] Furthermore, in step S6, the annealing temperature is 800-1000℃ and the time is 1 hour.

[0012] Furthermore, in step S5, the thickness of the nitrogen-doped carbon sealing layer is 1-5 nm; the chemical vapor deposition time is 5-20 minutes.

[0013] Further, in step S3, the washing and drying method is as follows: the etching product is repeatedly washed with deionized water and 0.1 M dilute hydrochloric acid until pH=7 to remove residual alkali and inorganic impurities, and then dried at 60~120℃ for 12 hours; the drying temperature is preferably 80~100℃.

[0014] Further, in step S1, the method for washing, drying, and powdering the fern is as follows: The dried fern plants are soaked in a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:1, and ultrasonicated for 10-60 minutes (preferably 20-40 minutes). The plants are washed 2-8 times (preferably 4-6 times) to remove impurities such as soil. After filtration, the plants are dried in a vacuum oven at 60-120 (preferably 80-100) °C for 8-20 hours (preferably 12-16 hours). After drying, the plants are ground or ball-milled to make the particle size of the powder less than 100 μm to obtain biomass powder.

[0015] Furthermore, the ferns selected are those containing natural nitrogen, oxygen, and trace amounts of silicon and calcium, such as true ferns, pine fern, or wedge-shaped fern. Alternatively, the ferns can be replaced with ethylene, propane, or liquid precursors such as acetone or ethanol vapor.

[0016] In another aspect, the present invention provides a fern-based hard carbon material, which is prepared by the method for preparing the fern-based hard carbon material.

[0017] In another aspect, the present invention provides the application of the aforementioned fern-based hard carbon material in the preparation of sodium-ion battery anodes. The beneficial effects of this invention are: This invention discloses a method for preparing fern-based hard carbon materials. The method involves weak etching with low-ratio KOH to create micro / mesoporous structures within the material, providing ion insertion channels. Then, low-temperature CVD surface sealing repairs and closes open pores, reducing surface active sites and constructing a multi-layered carbon structure combining internal insertion and external sealing. This results in a hard carbon material with high initial coulombic efficiency, high reversible capacity, and excellent cycle stability. The method utilizes widely available and low-cost raw materials, employs mild and controllable process parameters, and has relatively low energy consumption, making it suitable for large-scale production of sodium-ion battery anodes. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 The images show the XRD patterns of the materials prepared in Example 1, Comparative Example 1, and Comparative Example 3 of this invention. Figure 2 TEM image of the material prepared in Example 1; Figure 3 SEM image of the material prepared in Example 1; Figure 4 The first charge-discharge curve of the material prepared in Example 1; Figure 5 The first charge-discharge curve of the material prepared in Comparative Example 1; Figure 6 The first charge-discharge curve of the material prepared in Comparative Example 3. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] The principle involved in this invention: 1. The construction mechanism of the three-level structure A three-step synergistic process of low-specification activation, in-situ CVD, and rapid annealing was employed to construct a three-level structure consisting of an inner core layer, a transition layer, and an outer sealing layer on a fern precursor. Kernel layer: Employs a dual-source weak etching process using a low proportion of KOH and (NH4)2CO3, utilizing K... + Intercalation with NH4 + The synergistic effect of decomposition gases generates a limited network of micropores and mesopores within the material, avoiding excessive specific surface area and structural collapse caused by strong corrosion. This results in a porous sodium storage structure with localized micropores and disordered carbon layers, enabling precise control of sodium storage sites without increasing surface area through pore creation.

[0022] Transition layer: During the in-situ low-temperature CVD process of acetylene and NH3, NH4 + The active groups generated by decomposition interact with the material surface, forming a buffer interface between partially closed pores and oxygen and N functional groups. This not only blocks the intrusion of external impurities but also regulates the surface chemical properties through oxygen and N functional groups.

[0023] External sealing layer: An N-doped graphitized carbon layer of 1 to 5 nm is formed by acetylene thermal cracking deposition, which realizes the sealing of surface pores and the construction of a lightly doped passivation layer. At the same time, nitrogen doping is used to improve the electronic conductivity of the material and its affinity for sodium ions.

[0024] 2. The mechanism of synergistic regulation of structure and performance Low-specific-activation pore structure control: Dual-source weak etching avoids excessive specific surface area and structural collapse caused by strong corrosion, ensuring that the number and distribution of internal sodium storage sites are controllable, providing a structural basis for high reversible capacity, especially plateau capacity.

[0025] Simultaneous doping and sealing of pores in in-situ CVD: Acetylene is used as a carbon source to deposit an ultrathin carbon layer, and ammonia decomposition provides nitrogen atoms to achieve in-situ doping. Simultaneously, the external pores are sealed and the surface is passivated, which significantly reduces the specific surface area and surface active sites. At the same time, nitrogen doping improves electronic conductivity and sodium ion affinity.

[0026] Rapid annealing of the interface graphitization: By inducing local graphitization orientation of the carbon structure at the interface between the sealing layer and the hard carbon core through thermal stress, an efficient electron transport channel is constructed, improving the overall conductivity of the material without sacrificing the internal sodium storage structure.

[0027] 3. The natural advantages of fern precursors The natural heteroatoms contained in fern precursors, including N and O, can further participate in carbon layer doping and functional group formation in subsequent processes, synergistically improving the sodium storage performance, conductivity, and structural stability of the material.

[0028] This method utilizes the synergistic effect of a three-step process—low-specific activation, in-situ CVD, and rapid annealing—to prepare hard carbon materials that possess low specific surface area, high ICE (internal electrochemical conductivity), abundant internal sodium storage sites, high reversible capacity, good conductivity and structural stability, and excellent cycle performance. This provides an efficient performance regulation scheme for sodium-ion battery anode materials.

[0029] Example: Example 1 A method for preparing a fern-based hard carbon material includes the following steps: S1: Raw material pretreatment Ferns (taking true ferns as an example) were soaked in a mixture of anhydrous ethanol and deionized water (1:1 volume ratio), sonicated for 30 minutes, and washed 5 times to remove impurities such as soil. After filtration, they were dried in a vacuum oven at 100℃ for 16 hours. After drying, they were ground or ball-milled to make the particle size less than 100μm, yielding 10 g of fern biomass powder.

[0030] S2: Pre-carbonized The dried powder was placed in a tube furnace and heated to 400°C at 5°C / min under an inert atmosphere (nitrogen or argon). After holding at that temperature for 3 hours, it was cooled to obtain the pre-carbonized precursor (Pre-HC).

[0031] S3: Dual-source weak etching activation Fern powder was mixed with an activator at a mass ratio of KOH:(NH4)2CO3:Pre-HC = 0.1:0.04:1. The mixture was thoroughly ground until homogeneous. The mixture was then placed in a tube furnace and heated to 700°C at a rate of 5°C / min under a nitrogen atmosphere, and held at this temperature for 60 minutes. This process achieved ion migration and weak chemical etching, forming a confined microporous network within the particles. After cooling, the weakly etched sample (HC-A) was removed. This step achieves micro-activation, generating only limited micropores within the particles without forming a large specific surface area structure.

[0032] S4: Medium-temperature carbonization HC-A was repeatedly washed with deionized water and 0.1 M dilute hydrochloric acid until pH=7 to remove residual alkali and inorganic impurities; then dried at 100℃ for 12 hours. The dried sample was placed in a tube furnace and heated to 1200℃ at 5℃ / min under an inert atmosphere (nitrogen or argon), and held at that temperature for 3 hours. After cooling, the carbonized product HC-core was obtained.

[0033] S5: Acetylene + NH3, CVD in-situ sealing The HC-Core was placed in a CVD tube furnace. Under a nitrogen atmosphere, a mixture of acetylene and a small amount of ammonia was introduced (acetylene flow rate 4 sccm, ammonia flow rate 2 sccm, total gas flow rate 1000 sccm). Under protective conditions, the temperature was raised to 700℃ and deposited for 10 minutes. Acetylene thermally decomposed to form a carbon layer, and NH3 thermally decomposed to provide in-situ N doping, achieving surface pore sealing and lightly doped passivation layer construction to form a thin carbon layer of about 3 nm. After the carbon source was turned off, an inert atmosphere (nitrogen or argon) was continued to be introduced to cool to room temperature, obtaining the surface sealing product HC-seal.

[0034] (6) Post-processing The surface sealing product HC-seal was annealed at 850°C for 1 hour to improve film adhesion.

[0035] Example 2: The only difference between this embodiment and Example 1 is that in this embodiment, KOH:(NH4)2CO3:Pre-HC = 0.08:0.03:1; the CVD temperature in S5 is 700°C and the time is 15 min; the ammonia flow rate is 1.5 sccm. All other steps are the same as in Example 1.

[0036] Comparative Example Comparative Example 1: High KOH ratio for strong activation The only difference between this comparative example and Example 1 is that in this comparative example, step S3 is free of (NH4)2CO3, and the mass ratio of KOH to the pre-carbonized product is 1:1, indicating strong activation. The remaining steps are the same as in Example 1.

[0037] Comparative Example 2: Weak Etching with Low KOH Specificity The only difference between this comparative example and Example 1 is that in this comparative example, step S3 is weak etching, with no (NH4)2CO3 and a KOH to pre-carbonized product mass ratio of 0.1:1. The remaining steps are the same as in Example 1.

[0038] Comparative Example 3: No CVD sealing The only difference between this comparative example and Example 1 is that steps S5 and S6 are omitted in this comparative example, and the sealing is not performed. The remaining steps are the same as in Example 1.

[0039] Comparative Example 4: Acetylene CVD only The only difference between this comparative example and Example 1 is that in this comparative example, in step S5, there is no NH3 in the gas, but C2H2 is used, and the C2H2 flow rate is 10 sccm. The remaining steps are the same as in Example 1.

[0040] Comparative Example 5: No rapid annealing performed The only difference between this comparative example and Example 1 is that step S6 is omitted in this comparative example, while the remaining steps are the same as in Example 1.

[0041] Electrodes were prepared using the materials from Examples 1-2 and Comparative Examples 1-5, and their performance was tested. The electrode preparation methods are as follows (conventional methods): (1) The prepared active material, conductive agent SP carbon black and binder PVDF are mixed in a ratio of 90:5:5 (usually 80:10:10~95:2.5:2.5) and stirred into a uniform slurry; Other binders that can be used include sodium alginate, guar gum, PAA, LA132, LA133, chitosan, and CMC; other conductive agents that can be used include CNTs (carbon nanotubes) and graphene. (2) Use a coating machine (extrusion type, comma type, transfer type, etc.) to coat the slurry onto the current collector aluminum foil, and control the coating thickness and width; wet film thickness 50~200 μm (corresponding to dry film thickness 10~40 μm), coating speed: 0.5~2 m / min; (3) Remove the solvent by hot air drying or vacuum drying to form a solid electrode film; (4) The electrodes are compacted by a roller press to increase density and conductivity and reduce porosity; (5) The prepared electrodes and assembled batteries are subjected to performance tests.

[0042] Test results are as follows Figure 1-6 And as shown in Table 1; Table 1 Comparison of performance results of materials in Examples 1-2 and Comparative Examples 1-5

[0043] like Figure 1 The images shown are XRD images of the materials prepared in Embodiment 1, Comparative Example 1, and Comparative Example 3 of the present invention. Figure 1 As can be seen, the diffraction peak intensity of Example 1 is higher. The preparation method of Example 1 optimizes the stacking state of graphite sheets inside the fern-based hard carbon, enhancing the orderliness of the sheet arrangement, thus resulting in a stronger diffraction signal (CPS). The diffraction peak intensities of Comparative Examples 1 and 3 are relatively low, i.e., high KOH strong activation (Comparative Example 1) and no CVD sealing (Comparative Example 3), indicating a higher degree of disorder and weaker crystallinity in their hard carbon graphite sheets. XRD results show that the low-temperature CVD in-situ heteroatom sealing step in this method can regulate the microstructure of fern-based hard carbon and improve the orderliness of sheet stacking, which is a key step in optimizing the material structure.

[0044] Figure 2 TEM image of the material prepared in Example 1. Figure 2 The material in Example 1 shows a large number of closed-pore structures. Combined with the data in Table 1, it can be seen that it can reach 480mAh. g -1Of the total capacity, ICE accounts for 88.97%.

[0045] Figure 3 SEM image of the material prepared in Example 1. Figure 3 The material in Example 1 exhibits a uniform particle morphology with no loose structure, reflecting the process characteristic of creating pores without increasing surface area in Example 1. This regular and dense structural state provides a guarantee for the cyclic stability of the material. As shown in Table 1, its retention rate after 500 cycles reaches an excellent level of 91.1%.

[0046] Figure 4 The first charge-discharge curve of the material prepared in Example 1 shows a clear plateau in the low-voltage region, with a significant capacity proportion in the plateau. Combined with the data in Table 1, it can be seen that the first coulombic efficiency (ICE) of the material in Example 1 reaches 88.97%, and the plateau capacity is 284 mAh. g -1 The platform share reached 59.17%; at the same time, the material has abundant reversible sodium storage sites, achieving a capacity of 480mAh. g -1 The high total capacity demonstrates the significant improvement effect of this method on the sodium storage performance of the material.

[0047] Figure 5 The first charge-discharge curve of the material prepared in Comparative Example 1 is shown in Table 1. Based on the data, the ICE of this material is 76.4%, lower than that of Example 1. The data indicates that the strong corrosion treatment in Comparative Example 1 resulted in an excessively large surface area, leading to increased surface side reactions and a higher initial irreversible capacity. Furthermore, the strong corrosion treatment in Comparative Example 1 reduced its total capacity (382 mAh). g -1 Platform capacity (230mAh) g -1 The results were all significantly lower than those of Examples 1 and 2, and the retention rate after 500 cycles was only 72%, which was significantly lower than 91.1% in Example 1 and 88.2% in Example 2. This was directly related to the structural defects caused by strong corrosion leading to an excessively large surface area.

[0048] Figure 6 The first charge-discharge curve of the material prepared in Comparative Example 3 is shown in Table 1. As can be seen from the data, the ICE of the material in Comparative Example 1 is 74.62%, which is significantly lower than that in Example 1 and Example 2. This indicates that the lack of sealing in Comparative Example 3 leads to high side reactions, and the side reactions caused by the open pores on the surface improve the first irreversible capacity.

[0049] Comparing the data from Examples 1-2 and Comparative Example 2, it can be seen that Comparative Example 2 only uses KOH for weak etching, lacking the NH4+ generated by (NH4)2CO3. +The synergistic effect prevents the precise construction of an efficient internal sodium storage pore structure, thereby weakening the number of sodium storage sites and structural stability, which limits the total capacity to 420 mAh. g -1 The platform has a capacity of 230 mAh. g -1 The retention rate after 500 cycles was only 84%, which was lower than the data from Examples 1 and 2.

[0050] Comparing the data from Examples 1-2 and Comparative Example 4, it can be seen that Comparative Example 4 only used acetylene CVD treatment, lacking the nitrogen doping and thin carbon layer sealing provided by ammonia. This resulted in an inability to effectively seal the external pores and suppress side reactions, thus affecting the number of sodium storage sites and structural stability, leading to a total capacity of 410 mAh. g -1 The platform has a capacity of 240mAh. g -1 The retention rate after 500 cycles was only 83%, which was lower than the data from Examples 1 and 2.

[0051] Comparing the data from Examples 1-2 and Comparative Example 5, it can be seen that Comparative Example 5 omitted the rapid annealing step, lacking the optimization effect of rapid annealing on the interface structure, and thus failing to improve the interface conductivity, thereby affecting the stability of the material's sodium storage performance, resulting in a total capacity of 440mAh. g -1 The platform has a capacity of 260mAh. g -1 The retention rate after 500 cycles was only 86%, which was lower than the data from Examples 1 and 2.

[0052] In summary, the three-step synergistic process of low-specific activation, in-situ CVD, and rapid annealing adopted in this scheme can achieve high reversible capacity, high initial coulombic efficiency, and excellent cycle stability of the prepared materials, meeting the requirements of sodium-ion batteries for high energy density and long lifespan. This provides key material support for the commercial application of sodium-ion battery technology and lays the foundation for promoting the sustainable development of new energy storage and electric vehicle fields.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a fern-based hard carbon material, characterized in that, Includes the following steps: S1: Grind the washed and dried ferns into powder to obtain biomass powder; S2: Under an inert atmosphere, the biomass powder is heated to 300-500℃ and kept at that temperature for 1-5 hours to perform low-temperature pre-carbonization, thereby obtaining a pre-carbonized product. S3: Mix the pre-carbonized product with the activator in a mass ratio, heat to 600-800℃, keep warm for 30-90 minutes, cool and then perform weak etching activation to obtain the etched product, which is then washed and dried; the activator is a mixture of KOH and (NH4)2CO3; S4: The etched product after washing and drying is heated to 1000-1200℃ in an inert atmosphere and held for 1-6 hours to carbonize it and obtain a hard carbon core. S5: Under an inert atmosphere, the hard carbon core is placed in an environment of 600-800℃, and a mixed gas of acetylene, ammonia and inert gas is introduced to perform chemical vapor deposition, thereby depositing a nitrogen-doped carbon sealing layer on the surface of the hard carbon core to obtain a surface sealing product. S6: The surface sealing product is annealed under an inert atmosphere to obtain the fern-based hard carbon material.

2. The preparation method according to claim 1, characterized in that, In step S3, the mass ratio of KOH, (NH4)2CO3, and the pre-carbonized product is (0.05-0.2): (0.02-0.05):

1.

3. The preparation method according to claim 1, characterized in that, In step S5, the acetylene flow rate in the mixed gas is 3-5 sccm, the ammonia flow rate is 1-3 sccm, and the total flow rate of the gas for chemical vapor deposition is 1000 sccm.

4. The preparation method according to claim 1, characterized in that, In step S6, the annealing temperature is 800-1000℃ and the time is 1 hour.

5. The preparation method according to claim 1, characterized in that, In step S5, the thickness of the nitrogen-doped carbon sealing layer is 1-5 nm, and the chemical vapor deposition time is 5-20 minutes.

6. The preparation method according to claim 1, characterized in that, In step S3, the washing and drying method is as follows: the etching product is repeatedly washed with deionized water and 0.1 M dilute hydrochloric acid until pH=7, and then dried at 60~120℃ for 12 hours.

7. The preparation method according to claim 1, characterized in that, In step S1, the method for washing, drying, and powdering the fern plants is as follows: The dried fern plants are soaked in a 1:1 mixture of anhydrous ethanol and deionized water, sonicated for 10-60 minutes, and washed 2-8 times to remove impurities such as soil. After filtration, they are dried in a vacuum oven at 60-120℃ for 8-20 hours. After drying, they are ground or ball-milled to make the particle size of the powder less than 100μm to obtain biomass powder.

8. The preparation method according to claim 1, characterized in that, The ferns mentioned are true ferns, pine fern, or wedge-shaped fern.

9. A fern-based hard carbon material, characterized in that, It is prepared by the method for preparing fern-based hard carbon material according to claim 1.

10. The application of the fern-based hard carbon material according to claim 9 in the preparation of sodium-ion battery anodes.